The future of the hi-tech manufacturing industry in Thailand - Ang, Dennis Lien Lee (2008)
Despite the financial crisis in 1997 that affected most industries in Thailand, the hi-tech manufacturing industry was largely unaffected. Instead the hi-tech manufacturing industry was generating much-needed exports for the Thais to rebuild their economy. The hi-tech manufacturing industry, being a key contributor to Thailand's growth domestic product (GDP) growth, could eventually supersede agriculture and other traditional industries to become and remain as the main stream export industry for Thailand in the near future. The growth of the hi-tech manufacturing industry very much depended on government support and investments from foreign Multi National Companies (MNCs). However Thai culture and the lack of concerted efforts are prolonging the time for Thailand to go higher tech instead of currently lagging in medium-tech and labour intensive manufacturing industry. This report highlights the problems that Thailand is facing now and analyses the issues to predict the future direction of Thailand's hi-tech manufacturing industry.